DIGITAL PEDAGOGY: ENHANCING TEACHERS’ COMPETENCE IN TECHNOLOGY-BASED LEARNING MEDIA IN SMKS NGURAH RAI CANGGU - Ida Bagus Nyoman Mantra; Anak Agung Putu Arsana; A.A. Istri Yudhi Pramawati; I Gusti Agung Putri Wirastuti; Putu Sri Astuti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Teachers are expected to be able to improve their competencies, one of which is mastery of Information and Communication Technology. It is necessary to support enjoyable, effective, and efficient learning activities. This community service activity aims to improve teachers’ pedagogical competence and ability to create interactive learning media. The methods used in this training are lectures, demonstrations, and practice. The data collection technique uses a questionnaire regarding participants’ perceptions of the implementation of the training. Indicators of the success of this training include learning level, behavior level, reaction level, and result level. The results obtained from processing the data on all indicators were that participants agreed that the training had gone well. In contrast, most participants believed that the training had provided profound benefits and was very helpful in improving the participants’ personal quality.